Horse Housing on Prince Edward Island, Canada: Attitudes and Experiences Related to Keeping Horses Outdoors and in Groups - Megan Ross; Kathryn Proudfoot; Katrina Merkies; Ibrahim Elsohaby; Molly Mills; Kathleen Macmillan; Shawn Mckenna; Caroline Ritter (Animals, 2023)
Limited research has assessed the “human dimension” of horse care. The aims of this study were to (1) understand horse owner attitudes toward horse welfare when kept outdoors versus indoors and in groups versus individually, (2) compare horse owner attitudes toward horse welfare with the ways in which they house their horses, and (3) explore horse owner reasons for and challenges with their horses’ housing. Seventy-six horse owners in Prince Edward Island, Canada completed a questionnaire. Non-parametric tests and quantitative content analysis were used for data analysis. Consistent with the way horses were kept, most (82–96%) owners agreed that horses’ physical health, mental well-being, and natural living were better when kept outdoors and in groups. Fewer (64–68%) participants agreed that the horses’ standard of care was better when kept outdoors or in groups. Results show associations between owners whose attitudes suggest indoor and/or individual housing is better for horse welfare and keeping their horses indoors part-time and/or individually. Two overarching themes were developed from owners’ responses regarding their reasons and challenges related to the ways in which horses were housed: horse-centered and owner-centered care. The results indicate that horse owners’ choices about their horses’ housing correspond to beliefs about improved horse welfare.